Effect of Principal Leadership, School Culture and Pedagogic Competence Through Work Motivation on Teachers Performance - Ardliana, Benii; Rusdarti, Rusdarti; Suminar, Tri (Educational Management, 2021)
The purpose of this research is to analyze the direct and indirect effect of the principal leadership, school culture and teacher pedagogic competence on teacher performance through work motivation as an intervening variable. This research employs a quantitative approach with path analysis as the data analysis. The sample of this research is 114 teachers, consisting of 8 public high schools in Pati Regency and taken using proportionated cluster random sampling. Questionnaires were used as the research instrument. The results show that leadership, school culture, teacher pedagogical competence, and work motivation directly affected teacher performance. While on the indirect effect, work motivation was able to mediate the effect of leadership, school culture and pedagogic competence on teacher performance. The conclusion is that there is a direct effect of principal leadership, school culture and teacher pedagogic competence on teacher performance, and indirectly, work motivation is able to mediate the effect of the independent variables to the dependent one.